Designing and fabricating a stationary magnetic particle system for Non-destructive testing - Le , Duc Thinh; Nguyen , Duc Huyen; Nguyen , Xuan Thao; Pham , Thanh Tung; Ngo , Thi Kieu Oanh; Nguyen , Minh Duc; Duong , Thanh Tung (Nuclear Science and Technology, 2026)
The bench unit, also known as the stationary magnetic particle system or the wet horizontal system, has been designed and fabricated to incorporate both circular and longitudinal magnetization techniques. Its primary purpose is to test machine parts commonly used in various industries, including aviation, automotive, and railway. The system comprises several key components: a transformer, a current control unit, a parameter display and adjustment circuit, a head shot, a coil, and wet magnetic irrigation device. This system is in compliance with international standards and is ready for implementation in companies that require it